Identification of novel drug targets for primary open angle glaucoma and its potential side-effects by human plasma proteome - Da-Dong Jia; Qing-Ao Xiao; Shi-Yi Song; Meng Pan; Hao Hu; Kai-Li Wu; Jia-Bing Ran; Liang Liang (International Journal of Ophthalmology)
AIM: To explore whether plasma proteins serve as potential therapeutic targets for primary open angle glaucoma (POAG) based on a Mendelian randomization (MR) study. METHODS: Large-scale protein quantitative trait loci (pQTLs) data from the Icelandic deCODE database and two large POAG Genome-Wide Association Study (GWAS) summary datasets were used in this study. Causal associations between plasma proteins and POAG were identified using summary-data-based MR (SMR) analysis and the heterogeneity in dependent instruments (HEIDI) test. Colocalization analysis was then conducted to assess the genetic associations between these two factors. Phenotype-wide MR analysis was performed to validate protein targets as potential drug targets and to evaluate potential side effects. Finally, protein-protein interactions (PPI) were studied, and the Drug-Gene Interaction Database (DGIDb) was used to identify associations between drugs and the identified proteins. RESULTS: Four proteins (SVEP1, TMEM190, ROBO1, and ENPP5) were identified as potential drug targets in this study. Phenome-wide MR analysis showed that SVEP1, ROBO1, and ENPP5 were not associated with adverse effects, while TMEM190 was linked to nerve root and plexus disorders, as well as subarachnoid hemorrhage. Ticagrelor was suggested as a potential new drug for the treatment of glaucoma by regulating SVEP1. CONCLUSION: Four plasma proteins—SVEP1, TMEM190, ROBO1, and ENPP5—are identified as potential therapeutic targets for POAG through an MR approach. Phenome-wide MR analysis reveals that SVEP1, ROBO1, and ENPP5 are not associated with adverse effects, while TMEM190 is linked to nerve root and plexus disorders, as well as subarachnoid hemorrhage. Ticagrelor is proposed as a potential therapeutic drug for glaucoma by regulating SVEP1. These findings highlight the potential of plasma proteins as drug targets for POAG and provide valuable insights for further research.